Employee Performance Analysis at Bank Sultra Kaledupa District - Karsinah Sidi; A. Ifayani Haanurat; Andi Mappatompo Badawi (IECON: International Economics and Business Conference, 2025)
This study aims to find out how the performance of employees at Bank Sultra Kaledupa District and identify the factors that affect this performance and the efforts made to improve it. This study uses a qualitative approach by collecting data through interviews with employees from various divisions. The main focus of this research lies in how the role of human resources, work environment, and leadership affect the productivity and work effectiveness of bank employees. The results of this study conclude that employee performance at Bank Sultra Kaledupa District is influenced by various factors, both internal and external. Internal factors include work motivation, competence, discipline, and initiative. Meanwhile, external factors include supervisor support, technology systems, conducive work environment, and periodic performance evaluations. In improving employee performance, the management has made various efforts such as training, human resource development, and awarding for optimal performance. Seeing the results of this research, it is hoped that the management of Bank Sulawesi Kaledupa District can continue to provide guidance, provide adequate work facilities, and maintain good communication and cooperation in the work environment. Thus, employee performance will increase and have a positive impact on service to customers and the achievement of overall organizational goals.